Influence of Problem Based Instruction in Student with Learning Motivation Grade Toward Mastery of Biology Concept at Student Class X SMA Batik 1 Surakarta - Nur Eka Kusuma Hindrasti; Puguh Karyanto; Riezky Maya Probosari (BIO-PEDAGOGI, 2013)
The purposes of this research were to know: 1) the influence of Problem Based Instruction to the mastery of biology concept; 2) the influence of student’s learning motivation to the mastery of biology concept; 3) the interaction between learning model and learning motivation to the mastery of biology concept; and 4) the influence of better learning strategy to the mastery of biology concept. This research was quasi experiment research using Randomized Control Only design. Learning model and learning motivation were independent variables and mastery of biology concept was the dependent variable. The population of this research was all of  X grade of SMA Batik 1 Surakarta. The samples of this research were the students of class X-5 as the control class and students of class X-4 as the experimental class.  The sample of this research was established by cluster random sampling. The data about the result of study biology collected by use test and observation. Learning motivation meansured by using questionnaires. The analisis of this research was anava two away in different cell and the advance test used Bonfferoni test. The conclusion of this research were: 1) Problem Based Instruction had significant influence to the mastery of biology concept on X grade of SMA Batik 1 Surakarta; 2) Learning motivation had significant influence to the mastery of biology concept on X grade of SMA Batik 1 Surakarta; and 3) There wasn’t interaction between learning model and learning motivation to the mastery of biology concept on X grade of SMA Batik 1 Surakarta. Key Words: the mastery of biology concept, Problem Based Instruction, and learning motivation